0

Solve: -2x + 2 + x - 5 = 1 - 2x - x + 5

How do I solve
-2x + 2 + x - 5 = 1 - 2x - x + 5

Tamara J. | Math Tutoring - Algebra and Calculus (all levels)Math Tutoring - Algebra and Calculus (al...
4.9 4.9 (51 lesson ratings) (51)
2
-2x + 2 + x - 5 = 1 - 2x - x + 5

first, simplify the equation by combining any like terms on either side of the equation:

-2x + 2 + x - 5 = 1 - 2x - x + 5

-2x + x + 2 - 5 = 1 + 5 - 2x - x

-x - 3 = 6 - 3x

next, since we are looking to solve for x, move all terms with an x to one side of the equation and all other terms to the other side of the equation. in this case, we will add 3x to both sides of the equation then add 3 to both sides of the equation:

-x  -  3  =  6  -  3x
+3x                +3x
______________________
2x  -  3  =  6  +  0

2x  -  3  =  6
+3      + 3
______________________
2x  +  0  =  9

now we have the following:          2x = 9

to solve for x, divide both sides of the equation by 2:

2x/2 = 9/2

x = 9/2

Good description of the process - easy to understand.
~cr
Nikita D. | Certified Math Teacher- Pre algebra, Algebra, Algebra 2, GeometryCertified Math Teacher- Pre algebra, Alg...
4.9 4.9 (12 lesson ratings) (12)
1
First combine "like terms" on both sides of the equal sign.

-2x + 2 + x - 5 rewrite putting the like-terms together: (-2x + x + 2 - 5) becomes - x - 3

1 - 2x - x + 5 rewrite putting the like-terms together ( -2x - x + 1 + 5) becomes  -3x + 6

so now your equation is : - x - 3 = - 3x + 6

Now combine like terms on both sides of the equation

- add x to both sides: -3 = -3x + x + 6, which becomes  - 3 = - 2x + 6
- subtract 6 on both sides: -3 - 6 = -2x, which becomes -9 = -2x
solve for x by dividing by -2:,which gives you x =  -9/-2, x = 9/2, or  x =  4.5
Jim S. | Physics (and math) are fun, reallyPhysics (and math) are fun, really
4.7 4.7 (183 lesson ratings) (183)
0
Combining like terms gives -2x+x +2x + x = 6 + 3 or 2x= 9 x=9/2

Jim